Lactobacillus delbrueckii crl 581 differentially modulates tlr3-triggered antiviral innate immune response in intestinal epithelial cells and macrophages - Elean, Mariano Daniel (2021)
Lactobacillus delbrueckii subsp. lactis CRL 581 beneficially modulates the intestinal antiviral innate immune response triggered by the Toll-like receptor 3 (TLR3) agonist poly(I:C) in vivo. This study aimed to characterize further the immunomodulatory properties of the technologically relevant starter culture L. delbrueckii subsp. lactis CRL 581 by evaluating its interaction with intestinal epithelial cells and macrophages in the context of innate immune responses triggered by TLR3. Our results showed that the CRL 581 strain was able to adhere to porcine intestinal epithelial (PIE) cells and mucins. The CRL 581 strain also augmented the expression of antiviral factors (IFN-α, IFN-β, Mx1, OAS1, and OAS2) and reduced inflammatory cytokines in PIE cells triggered by TLR3 stimulation. In addition, the influence of L. delbrueckii subsp. lactis CRL 581 on the response of murine RAW macrophages to the activation of TLR3 was evaluated. The CRL 581 strain was capable of enhancing the expression of IFN-α, IFN-β, IFN-γ, Mx1, OAS1, TNF-α, and IL-1β. Of note, the CRL 581 strain also augmented the expression of IL-10 in macrophages. The results of this study show that the high proteolytic strain L. delbrueckii spp. lactis CRL 581 was able to beneficially modulate the intestinal innate antiviral immune response by regulating the response of both epithelial cells and macrophages relative to TLR3 activation.